2017
DOI: 10.1002/cssc.201701016
|View full text |Cite
|
Sign up to set email alerts
|

Wacker Oxidation of Terminal Alkenes Over ZrO2‐Supported Pd Nanoparticles Under Acid‐ and Cocatalyst‐Free Conditions

Abstract: Highly efficient Wacker oxidation of aromatic or aliphatic terminal alkenes into methyl ketones and benzofurans is developed by using reusable Pd nanoparticles (NPs) supported on ZrO under acid- and cocatalyst-free conditions. Molecular oxygen or air can be utilized as the terminal oxidant, which results in the formation of H O as the only theoretical byproduct. The activation of the Pd NPs by O plays an important role in promoting this reaction. Interestingly, PdO supported on ZrO showed no activity. Addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 61 publications
(28 reference statements)
1
25
0
Order By: Relevance
“…Heterogeneous Pd‐catalyzed protocols based on the use of molecular oxygen now represent a highly promising and versatile approach to achieving this goal. Examples of dehydrogenation reactions or Wacker processes, of C−H functionalization and of C−C bond formation through heterogeneous Pd‐catalyzed aerobic oxidation have recently been reported. Representative examples of the latter type of reaction include the oxidative coupling of carbon nucleophiles such as arylboronic acids to obtain biaryls, or the Glaser‐Hay reaction to synthesize diynes …”
Section: Introductionmentioning
confidence: 99%
“…Heterogeneous Pd‐catalyzed protocols based on the use of molecular oxygen now represent a highly promising and versatile approach to achieving this goal. Examples of dehydrogenation reactions or Wacker processes, of C−H functionalization and of C−C bond formation through heterogeneous Pd‐catalyzed aerobic oxidation have recently been reported. Representative examples of the latter type of reaction include the oxidative coupling of carbon nucleophiles such as arylboronic acids to obtain biaryls, or the Glaser‐Hay reaction to synthesize diynes …”
Section: Introductionmentioning
confidence: 99%
“…26 27 First, styrene (16a) was chosen as a model substrate for Wacker oxidation, and the reaction conditions were optimized using Pd/ZrO 2 ( Table 8). Screening of solvents (entries 1 6) revealed that MeOH was suitable (entry 4).…”
Section: Wacker Oxidationmentioning
confidence: 99%
“…Relation between Pd particle size and catalytic activity for Wacker oxidation of stryrene (16a). 27 The interaction and stabilization of positively charged Pd species on these metal oxides may contribute to activation of the Pd surface for allylic C H acetoxylation and Wacker oxidation.…”
Section: Wacker Oxidationmentioning
confidence: 99%
“…Some ZrO 2 -supported catalysts show higher activities compared to other supported catalysts for the oxidation of carbon monoxide, methane, etc [10][11][12][13][14][15]. In addition to gas-phase oxidation, ZrO 2 has also been applied to liquid-phase oxidation, and ZrO 2 -supported catalysts have demonstrated promising results in processes such as selective oxidation [16][17][18] and wastewater pollutant treatment, e.g. Kraft plant wastewater [19], carboxylic acid [20,21], N, N-dimethylformamide [22].…”
Section: Introductionmentioning
confidence: 99%